Evaluasi Kinerja Saluran pada Sistem Drainase Kawasan UPN “Veteran” Jawa Timur - Muchammad Ali Fikri; Syadzadhiya Qothrunada Zakiyayasin Nisa’; R Mohammad Alghaf Dienullah (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2026)
The drainage system is critical infrastructure for managing stormwater runoff in densely built urban areas, including higher education institutions. This study aims to evaluate the capacity performance of the existing drainage channels in the UPN "Veteran" Jawa Timur campus area. The evaluation was conducted through two main stages: hydrological analysis using the rational method to estimate the design runoff discharge for a 10-year return period, and hydraulic analysis using Manning's equation to calculate the channel cross-sectional capacity in accordance with Permen PU No. 12 of 2014. Based on the assessment of 43 drainage channels, the results showed that 33 channels (76.7%) are still functioning optimally and capable of accommodating the design discharge. Conversely, 10 channels (23.3%) were identified as having insufficient capacity. This capacity deficit was triggered by initial designs that did not accommodate the 10-year return period flood discharge, increased runoff coefficients due to massive pavement development, and effective cross-section narrowing caused by sedimentation. To mitigate inundation issues, this study recommends redesigning the failing channels using an economical hydraulic cross-section, accompanied by periodic normalization and dredging for functional channels. The findings of this study are expected to serve as technical guidelines for the optimal and sustainable management of campus drainage infrastructure.